2021
DOI: 10.1016/j.neuroimage.2020.117571
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation artifact source separation (SASS) for assessing electric brain oscillations during transcranial alternating current stimulation (tACS)

Abstract: Highlights Stimulation Artifact Source Separation (SASS) is introduced, a real-time compatible signal decomposition algorithm for separating electric brain activity and stimulation signal artifacts related to amplitude-modulated transcranial alternating current stimulation (AM-tACS) Employing SASS, phase and amplitude of single-trial steady state visual evoked potentials (SSVEPs) were reliably recovered from electroencephalography (EEG) recordings at the frequency targeted w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 39 publications
1
37
0
1
Order By: Relevance
“…The field of tACS research has benefitted greatly from amplitude-modulated tACS (Witkowski et al, 2016; Negahbani et al, 2018; Haslacher et al, 2021), where the carrier frequency (usually a very high frequency; e.g., 220 Hz) is purposely amplitude modulated at the frequency of physiological interest (e.g., 10 Hz). If the modulation frequency (envelope) can itself reliably entrain neural activity at that frequency, then the problem of nonlinear modulations will be shifted into the higher frequency domain, and will instead occur symmetrically around the carrier, and symmetrically around the carrier plus-and-minus the modulation frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field of tACS research has benefitted greatly from amplitude-modulated tACS (Witkowski et al, 2016; Negahbani et al, 2018; Haslacher et al, 2021), where the carrier frequency (usually a very high frequency; e.g., 220 Hz) is purposely amplitude modulated at the frequency of physiological interest (e.g., 10 Hz). If the modulation frequency (envelope) can itself reliably entrain neural activity at that frequency, then the problem of nonlinear modulations will be shifted into the higher frequency domain, and will instead occur symmetrically around the carrier, and symmetrically around the carrier plus-and-minus the modulation frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods exist for recovering the M/EEG from artefacts of tACS (Herrmann and Strüber, 2017; Kasten and Herrmann, 2019), with varying degrees of complexity and success. These methods include spatial filtering (beamforming, Neuling et al, 2015; Noury et al, 2016; Witkowski et al, 2016; ‘SASS,’ Haslacher et al, 2021), temporal filtering (notch, Voss et al, 2014; Hampel, Santos Monteiro et al, 2015), variations of template subtraction (Voss et al, 2014; Kohli and Casson, 2015, 2019; Noury et al, 2016; Dowsett and Taylor, 2017; Guggenberger and Gharabaghi, 2018), principal component analysis (PCA, Kohli and Casson, 2015; Santos Monteiro et al, 2015), and a combination of the latter two (Helfrich et al, 2014; Noury et al, 2016). Universally, these approaches assume linear stimulation artefacts— either time-invariance (i.e., an artefact is a scaled version of itself from cycle to cycle) or sensor-invariance (i.e., artefacts are scaled versions of one another from sensor to sensor).…”
Section: Introductionmentioning
confidence: 99%
“…However, through computer simulation, Kasten found that even the weak nonlinearity of the stimulation and recording hardware also lead to disordered modulation of the frequency and its harmonics, and artifacts are still present in the stimulation process (Kasten et al, 2018). Therefore, in view of the artifacts still existing in AM-tACS, David successfully separated the stimulus artifacts in AM-tACS through a real-time compatible artifact suppression algorithm and verified it in seven healthy volunteers (Haslacher et al, 2020).…”
Section: Interference Modulation Electrical Stimulationmentioning
confidence: 92%
“…The copyright holder for this preprint this version posted April 13, 2021. ; https://doi.org/10.1101/2021.03.26.437107 doi: bioRxiv preprint Amplitude-modulated tACS (AM-tACS) was proposed as a promising way to allow for effective magnetoencephalography (MEG) or EEG signal reconstruction during electrical stimulation [62][63][64][65]. However, similar to TI stimulation, studies on AM-tACS have also mostly focused on simulations, and no systematic experimental test to validate the effectiveness of AM-tACS on humans has been performed.…”
Section: Ti Stimulation Is Effective In the Human Motor Cortexmentioning
confidence: 99%